DLCO: adjust for lung volume, standardised reporting and interpretation. Issue 2 (24th August 2017) - Graham, Brian L.; Brusasco, Vito; Burgos, Felip; Cooper, Brendan G.; Jensen, Robert; Kendrick, Adrian; MacIntyre, Neil R.; Thompson, Bruce R.; Wanger, Jack
D.C. Johnson proposed that an adjustment of the predicted value for the diffusing capacity of the lung for carbon monoxide ( D LCO ) based on the measured and predicted lung volume be included in the report of D LCO test results. An interpretation algorithm is also proposed. A correction of the predicted value for D LCO based on the measured lung volume is not recommended http://ow.ly/KFn730cPJ9n